Kajian perbandingan pencapaian akademik pelajar-pelajar bermasalah pendengaran yang memakai alat bantu pendengaran dan yang memakai alat bantu pendengaran di sekolah pendidikan khas di Kelantan - Khairul Annuar, Jamil (Universiti Sains Malaysia, 2009)
This research is aimed to study the mutual relationship of using hearing aid with academic achievements directly. The comparison is made on student's academic achievement based on Ujian Penilaian Sekolah Rendah (UPSR), hearing aid usage and teacher's knowledge on hearing aids. Hundred and one (101) students and twenty seven (27) teachers from SKPK Kelantan, Lati, Pasir Mas were selected as the subjects of the study. The data was computed and analyzed by using Statistical Package for Social Science (SPSS) 14. Descriptive study such as percentage was utilized in order to relate the student's academic achievements, hearing aid usage and teacher's awareness about the hearing aids. The outcome of the study showed that there were possible links between hearing aid usage and student achievement in Malay language (Bahasa Melayu) in students with hearing difficulty. The study also found that the application of hearing aid in students are low with 62.4% did not have hearing aid, 26.7% have the aids but did not used it while only 10.9% have and used the hearing aid. This study also able to show that the teacher's basic skills in routine check of the hearing aid is low. The limitation and implication in this study was also discussed.